2022
DOI: 10.3390/biom12070916
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of micro-RNA, mRNA and eIF Expression in Tamoxifen-Adapted MCF-7 Breast Cancer Cells: Impact of miR-1972 on Gene Expression, Proliferation and Migration

Abstract: Background: Tamoxifen-adapted MCF-7-Tam cells represent an in-vitro model for acquired tamoxifen resistance, which is still a problem in clinics. We here investigated the correlation of microRNA-, mRNA- and eukaryotic initiation factors (eIFs) expression in this model. Methods: MicroRNA- and gene expression were analyzed by nCounter and qRT-PCR technology; eIFs by Western blotting. Protein translation mode was determined using a reporter gene assay. Cells were transfected with a miR-1972-mimic. Results: miR-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Several deregulated genes identified by these means have been shown to have an impact on the prognosis of breast cancer patients. We have reported on gene expression changes in such a cellular model, focusing on lncRNAs [ 10 ], and extended this investigation on microRNAs and eukaryotic initiation factors [ 39 ]. We report herein on further studies on LINC00992, a long non-coding RNA that is down-regulated is response to long-term exposure of MCF-7 cells to low doses of 4OH-tamoxifen (10 nM) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several deregulated genes identified by these means have been shown to have an impact on the prognosis of breast cancer patients. We have reported on gene expression changes in such a cellular model, focusing on lncRNAs [ 10 ], and extended this investigation on microRNAs and eukaryotic initiation factors [ 39 ]. We report herein on further studies on LINC00992, a long non-coding RNA that is down-regulated is response to long-term exposure of MCF-7 cells to low doses of 4OH-tamoxifen (10 nM) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell growth inhibition rate, IC 50 , and reversal fold (RF) after combination drug treatment were calculated. 21 = RF IC IC 50 50 drug combination drug alone (4) where IC 50drug alone is the cell median inhibition rate of TAM on MCF-7/TAM cells, IC 50drug combination is the cell median inhibition rate of TAM-API combination treatment with nontoxic concentrations of IMP-RH60/mPEG−PLLA on MCF-7/TAM cells.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…4,9,21,44 Despite this established ER receptor actions, we acknowledged that ET resistance is multifactorial and we cannot exclude several other non-estrogen related pathways in several studies using tamoxifen and fulvestrant adapted cell lines. [51][52][53][54] Progesterone and progesterone receptor Progesterone is a steroid hormone produced by the corpus luteum in the human ovarium, which its primary duty is to prepare the female body for gestation. Breast epithelial cells are indispensable in affecting duct-alveolar changes in phases such as puberty, the luteal phase (pre-menstrual period), pregnancy, and lactation.…”
Section: Estrogen and Estrogen Receptormentioning
confidence: 99%
“…Distinguished studies also showed us that numerous studies of non-coding RNA especially miRNA play important roles in ET resistance, such as miRNA such as miRNA-1972, miRNA-375 and miRNA-221. 52,88 However there are still no clear depiction of p53 roles in ET resistance caused by miRNA involvement. It is due to the complexity of the network of both parties, in which miRNA could regulate p53 level and function and vice versa mutated p53 could regulate the miRNA expression and modulate miRNA biology activities due to its gain-of-function properties.…”
Section: Estrogen and Estrogen Receptormentioning
confidence: 99%
See 1 more Smart Citation